PENGARUH SUBSTITUSI DAUN KELOR DAN TULANG IKAN BANDENG TERHADAP EVALUASI SENSORI DAN KANDUNGAN GIZI MIE INSTAN - Imroatul Mukarromah; Dian Agnesia; Amalia Rahma (Universitas Muhammadiyah Gresik, 2021)
This study aims to was used to analyze the effect of substitution of Moringa oleifera and milkfish bones on the sensory evaluation and nutritional content of instant noodles with the best formula. This study design was Eksperimental with a Completely Randomized Design (CRD). There are four (4) comparative concentration treatments (control, 3:1, 2:2, and 1:3) which were carried out by hedonic tests of untrained panelists and children, then the best formula instant noodles are tested for nutritional content in the laboratory. The sampling technique used simple random sampling as many as 30 mothers of children under five and their toddlers who met the inclusion criteria. Analysis of sensory evaluation data used the statistical Kruskal-Wallis test with the further test Mann-Whitney, while the analysis of the nutrient content data used a different test (T-Test for carbohydrates, protein, calcium, iron, water, and Mann-Whitney for fat). Overall the results of the hedonic test of the parameters of color, flavor, taste, texture, and acceptance of instant noodles as a whole had a real or significant difference between the control and substitution formulas with a significant value of p≤0.05. The best formula from the hedonic test results was the F2 formula (substitution of Moringa oleifera and milkfish bones 2:2). The test results for the nutritional content of carbohydrates, protein, fat, calcium, iron, and water content also differed significantly between the control formula and the best formula (F2) with a significant value of p≤0.05. The conclusion of this study is there was an effect of substitution of Moringa oleifera and milkfish bones on sensory evaluation and nutritional content of instant noodles.